Analisis Kemudahan Penggunaan, Efisiensi dan Keamanan Terhadap Minat Nasabah Bertransaksi Menggunakan BSM Mobile Banking Pada Bank Syariah Mandiri Kantor Cabang Payakumbuh - Sandra Dewi; Sabri Sabri; Vina Pandu Winata (Institut Agama Islam Negeri (IAIN) Bukittinggi, 2018)
This study aims to determine the effect of ease of use, efficiency and security on the interest in transactions using BSM Mobile Banking. To conduct discussions and research, using primary data directly obtained from the object of research through a structured list of statements or questionnaires that have been answered by respondents, this study uses the help of SPSS version 15, and data testing techniques use binary logistic regression analysis. The results of the analysis show that ease of use, efficiency and security have a positive and significant influence on the interest in transacting using BSM Mobile Banking, both partially and simultaneously. The most dominant variable influencing the interest in transacting using BSM Mobile Banking is efficiency.